Relationships between Connectedness, Performance Proficiency, Satisfaction, and Online Learning Continuance - Tseng, Hungwei; Kuo, Yu-Chun; Yeh, Hsin-Te; Tang, Yingqi (Online Learning, 2022)
Maintaining momentum is vital in terms of how soon students can complete a program, especially for those who are in the early stage of taking online courses. This study attempted to extend the existing literature by examining the influence of online students’ perceived sense of connectedness, performance proficiency, and satisfaction on their intentions to continue an online learning course. A quantitative survey approach was adopted to test our hypothesized structural model. Three hundred and sixty-nine students who had taken fewer than three fully online courses participated in this study. The results revealed that three out of four testing hypotheses were all supported at the 0.01 significance level, and one of the path coefficients indicated that online students’ confidence in their ability or competency to perform academic tasks did not directly influence their intention to take future online courses. Instead, the influence of performance proficiency on online learning continuance intention was mediated through the factor of satisfaction. In addition, satisfaction was found to have a significantly direct impact on online learning continuance intention, suggesting that when students taking online courses are satisfied with their online learning experience, the likelihood for them to continue taking other online courses is higher.